Mobile Savings Application With Gamification (Msag) - Gan, Kar Hou (2022)
Mobile Savings Application with Gamification is an application that can do more than just enable you to check daily transaction, balances, and adding daily income or expenses. They can also help you save and manage your finances with a more attractive way. For example, offering rewards, achievement. The objectives of this project are to study on gamification technique to encourage user using mobile saving application with gamification. In this application, the Waterfall Model has been used as a methodology for application development. Waterfall Model has 6 phases which are requirements, analysis, design, coding, testing and implementation. The testing plan that would use in this project is User Acceptance Testing (UAT) and Functionality Testing (FAT). The outputs are public since it is a public used mobile application.